Transparency and accountability analysis of village fund allocation management in Lembang Polopadang village - Jemi Pabisangan Tahirs (Institute of Computer Science (IOCS), 2023)
The Village Fund program aims to provide financial support to encourage economic, social, and infrastructure development in rural areas. Village funds take the form of financial transfers directly to village governments. These funds can be used for infrastructure development, local economic development, health and education services, and the development of other village potentials. The purpose of village funds is to reduce the development gap between urban and rural areas and its management with the principles of transparency, community participation, accountability, and management based on local needs and potential. The research objective is to explore more deeply how transparency and accountability in the management of village funds to improve the effectiveness of village fund management in Lembang Polopadang. The data analysis techniques used are data reduction, data display, data verification, data categorization, data interpretation and conclusion drawing. The results showed that the village's financial management has fulfilled the provisions stipulated in Permendesa No. 7 of 2021 concerning Priorities for the Use of Village Funds in 2022. Transparency and accountability in the management of ADD in Lembang Polopadang have been carried out properly at the planning, implementation, administration, reporting, and accountability stages. Information regarding activities or programs financed by ADD has been well produced. In addition, physical and administrative accountability has also run well in accordance with applicable village regulations. This shows the village government's commitment to improving the welfare of the population through transparent and accountable ADD management.